The association between pulmonary embolism and the cancer-related genomic alterations in patients with NSCLC - Xiong, Wei (Respir Res, 2020)
To date, the association between the acute pulmonary embolism (PE) and the currently existing cancer-related genomic alterations in patients with non-small cell lung cancer (NSCLC) has been understudied. We reviewed patients with a confirmed histopathological diagnosis of NSCLC who underwent computed tomography pulmonary angiography (CTPA) and molecular tests including ALK, ROS1, EGFR, BRAF V600E as well as PD-L1 during the diagnosis of NSCLC, to explore the association between the genomic alterations and PE. The results showed that, for the patients with positive results of genomic alterations, the proportion of positive ALK (13.6%vs8.5%, P<0.001) and PD-L1 (24.7%vs19.9%, P = 0.001) in PE group were more than those in Non-PE group. The patients with positive ALK and PD-L1 had the most (19.0%) and second most (15.4%) incidence of PE among all the patients being studied. A multivariate Logistic regression analysis showed that the positive ALK [1.685(1.065–2.215)(P<0.001)] and PD-L1[1.798(1.137–2.201)(P<0.001)] were correlated with the occurrence of PE. The positive results of ALK and PD-L1 genomic alterations may indicate an increased risk of pulmonary embolism in patients with NSCLC.